2010
DOI: 10.1097/jom.0b013e3181f72b7c
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Cancer Incidence in the Agricultural Health Study

Abstract: Objective-Our objective is to re-evaluate cancer incidence among Agricultural Health Study participants. Methods-Standardized incidence ratios (SIR) and Relative Standardized Ratios were calculated.Results-A significant excess of prostate cancer was seen for private and commercial applicators, SIR = 1.19 (95% Confidence Interval (CI) 1.14, 1.25) and SIR = 1.28 (95% CI 1.00, 1.61), respectively. Excesses were observed for lip cancer, SIR = 1.97 (95% CI 1.02, 3.44), and multiple myeloma, SIR = 1.42 (95% CI 1.00,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
114
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 69 publications
(59 reference statements)
11
114
4
1
Order By: Relevance
“…In one of the largest prospective studies of pesticide exposures published to date, the Agricultural Health Study (AHS), which was conducted in Iowa and North Carolina, a small but significant excess prostate cancer risk was CA CANCER J CLIN 2013;63:120-142 VOLUME 63 _ NUMBER 2 _ MARCH/APRIL 2013 observed among both farmers (19% excess) and commercial pesticide applicators (28% excess). 21 Among the 1962 incident prostate cancer cases that developed in the AHS cohort from 54,412 pesticide applicators that were cancer free at the start of the observation period, 21 26 although no studies have determined whether these 2 OPs can cause DNA damage in mammalian cells. In addition, the recent study by Koutros et al 25 demonstrated that a significantly increased risk of prostate cancer was observed among men with documented exposure to fonofos or aldrin and a family history of prostate cancer, whereas there was no increased risk among men without a family history.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the largest prospective studies of pesticide exposures published to date, the Agricultural Health Study (AHS), which was conducted in Iowa and North Carolina, a small but significant excess prostate cancer risk was CA CANCER J CLIN 2013;63:120-142 VOLUME 63 _ NUMBER 2 _ MARCH/APRIL 2013 observed among both farmers (19% excess) and commercial pesticide applicators (28% excess). 21 Among the 1962 incident prostate cancer cases that developed in the AHS cohort from 54,412 pesticide applicators that were cancer free at the start of the observation period, 21 26 although no studies have determined whether these 2 OPs can cause DNA damage in mammalian cells. In addition, the recent study by Koutros et al 25 demonstrated that a significantly increased risk of prostate cancer was observed among men with documented exposure to fonofos or aldrin and a family history of prostate cancer, whereas there was no increased risk among men without a family history.…”
Section: Prostate Cancermentioning
confidence: 99%
“…155 In a follow-up study, a 1.42-fold (95% CI, 1.00-fold to 1.81-fold) risk of multiple myeloma was observed among cohort members in North Carolina compared with the rest of the state, but a similar excess risk was not observed in Iowa. 21 The cause of this excess could not yet be explained, but a separate analysis of the AHS cohort observed a statistically significant risk of multiple myeloma among pesticide applicators in the highest exposure group for the insecticide permethrin (RR, 5.72; 95% CI, 2.76-11.87 [P value for trend ¼ .01]) compared with never-users. 156 A cautious interpretation of these results is warranted because the analysis was driven by only 10 exposed cases in the highest exposure group.…”
mentioning
confidence: 99%
“…More recent systematic review studies or case-control studies reported positive association between exposure to pesticides and several cancers including prostate cancer (Van Maele-Fabry and Willems, 2004;Koutros et al, 2010;Doolan G et al, 2014), non-Hodgkin lymphoma (NHL) (Merhi et al, 2007;Balasubramaniam et al, 2013;Yildirim et al, 2013;Schinasi and Leon, 2014), leukemia (Merhi et al, 2007;Van Maele-Fabry et al, 2008), multiple myeloma (Merhi et al, 2007) and lung cancer (Ganesh et al, 2011;Luqman et al, 2014). In the case of esophageal or gastric cancer, no relationship with pesticide usage was reported in recent Turkey study (Yildirim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The scatter and residues from these pesticides can cause serious pollution (Ghimire and Woodward 2013) and great harm (Wang et al 2013), including many diseases to humans (Jaga and Dharmani 2005;Koutros et al 2010) Pesticides can affect human and animal genome epigenetic status (Collotta et al 2013) thereby causing high incidences of a variety of cancers (Zhang et al 2012a, b;Weichenthal et al 2010). Some exogenous chemicals can cause methylation changes in plant genomic DNA (Karan 2012;Tyunin et al 2012).…”
Section: Introductionmentioning
confidence: 98%